A current‐limiting DC circuit breaker with power flow control capability. Issue 9 (14th February 2022) - Xue, Shimin; Chen, Xiao; Liu, Baibing; Chen, Wenjie; Li, Botong; Li, Bin
Abstract: Power flow controller (PFC), fault current limiter (FCL) and DC circuit breaker (DCCB) are important equipment in the DC grid. There are a large number of power electronic components in these equipment, resulting in high cost. In order to reduce the use of additional components, a current‐limiting DC circuit breaker with power flow control capability is proposed here, which integrates the PFC, FCL, and DCCB into one equipment. Further, the main breaker in the proposed circuit breaker is shared by all lines connected to a DC bus to reduce cost. The topology and operating principle of the circuit breaker are introduced. Theoretical analysis and parameter design are carried out. Besides, the proposed circuit breaker is verified in PSCAD/EMTDC. Finally, the performance and cost are compared with existing schemes. The simulation results show that the proposed circuit breaker can effectively realize power flow control, current limiting and fault isolation at a lower cost.